Dose reconstruction including dynamic six-degree of freedom motion during prostate radiotherapy. (August 2019) - Muurholm, C G; Ravkilde, T; Skouboe, S; Eade, T; Nguyen, D T; Booth, J; Keall, P J; Poulsen, P R
Abstract: An in-house developed program for real-time reconstruction of motion-induced dose errors, DoseTracker, was extended to handle rotational target motion in addition to the previously implemented translational motion, and applied offline for prostate VMAT treatments. For translational motion, the motion-induced errors of DoseTracker were in good agreement with ground truth dose reconstructions performed in a commercial treatment planning system. For rotational motion, no ground truth was available, but DoseTracker showed that the VMAT dose is highly robust against static interfractional rotations but quite sensitive to dynamic intrafraction rotations due to interplay effects between target motion and machine motion.